Anti-Angiogenic and Cytotoxicity Effects of Selachyl Alcohol Analogues - Momha, René; Le Bot, Damien; Mosset, Paul; Legrand, Alain B. (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: The active ingredients in the shark liver oil (SLO) mixture were found to be a group of etherlinked glycerol known as alkylglycerols (AKGs). During the last century, initial clinical use of the SLO mixture was for treating leukemias and later preventing radiation sickness from cancer x-ray therapy. Selachyl alcohol is one of the most abundant AKGs in the SLO mixture and it displayed strong activity in reducing lung metastasis number on a model of grafted tumor in mice (Lewis lung carcinoma cells). Objectives: In this study, selachyl alcohol analogue containing methoxyl (7), gem-difluorinated (8), azide (9) and hydroxyl (10) group at the 12 position in the alkyl chain were synthesized and compared regarding their cytotoxicity and anti-migratory effects on Human Umbilical Vein Endothelial Cell line. Methods: AKGs 7-10 were synthesized according to the literature procedure. The cytotoxicity of the studied AKGs was evaluated by the MTT test and Human Umbilical Vein Endothelial Cell line (HUVEC) was used as an in vitro model to evaluate their anti-migratory effects. Results: The four AKGs have substantially the same toxicity threshold (≥ 12 μM), whereas they have an anti-migratory activity significantly different on endothelial cells. AKGs 9 and 10 significantly reduce the chemotactic migration induced by VEGF, but analogue (10) containing the hydroxyl group at the 12 position in the alkyl chain was the most potent anti-VEGF inhibitor. Conclusion: We presented here a series of four synthetic selachyl alcohol analogues, among which AKGs 9 and 10 showed the ability to inhibit endothelial cell migration. The relationship structures and anti-VEGF effects of these analogues were also evaluated and discussed. Unnatural synthesized AKGs could be explored as one new source of anticancer agents.
Keywords: endothelial cell migration